Synthesis of 3,4-dihydro-1,8-naphthyridin-2(1H)-ones via microwave-activated inverse electron-demand Diels–Alder reactions - Fadel, Salah; Hajbi, Youssef; Khouili, Mostafa; Lazar, Said; Suzenet, Franck; Guillaumet, Gérald (Beilstein Journal of Organic Chemistry, 2014)
Substituted 3,4-dihydro-1,8-naphthyridin-2(1H)-ones have been synthesized with the inverse electron-demand Diels–Alder reaction from 1,2,4-triazines bearing an acylamino group with a terminal alkyne side chain. Alkynes were first subjected to the Sonogashira cross-coupling reaction with aryl halides, the product of which then underwent an intramolecular inverse electron-demand Diels–Alder reaction to yield 5-aryl-3,4-dihydro-1,8-naphthyridin-2(1H)-ones by an efficient synthetic route.
Keywords: inverse-electron-demand Diels–Alder reaction; microwave irradiation; naphthyridin-2(1H)-ones; Sonogashira cross-coupling; 1,2,4-triazine